PERFORMANCE OF AUS RICE IN DIFFERENT TILLAGE SYSTEMS AND CROP ESTABLISHMENT METHOD IN SOUTHWEST BANGLADESH - SHARIF AHMED, LATIFUL BARI, (Journal of Experimental Sciences)
High labor wage and irrigation water scarcity are the major constraints to becoming rice production less profitable and unsustainable in Bangladesh. To address these problems, rice production needed less water and less labor consuming production technologies. In traditional rice production systems which is puddled-transplanted rice (PTR), a significant amount of water and labor are used for tillage (wet) and transplanting operations. A farmers’ participatory on-farm trial was conducted to evaluate the performance of aus rice at different tillage systems and crop establishment methods in the southern part of Bangladesh. Wet tillage (puddled systems) to dry-tillage and transplanted rice to direct dry-seeded rice (DSR) may have the potential to reduce production cost by using less labor and water, resulting in higher profit. The trial examined tillage systems (strip tillage, reduced tillage and puddling) and crop establishment methods (direct dry-seeded and transplanted) in six farmers’ fields in aus 2015. Crop established by reduced-and strip-tillage in DSR conditions reduced crop duration by 7 d compared to PTR. Grain yield (4.4-4.6 t ha-1) was similar in DSR which is established by reduced-and strip-tillage conditions and PTR; however, total production cost in DSR was 15-18% lower than the PTR. Slightly higher but significantly similar gross income was recorded in PTR than DSR, however, net profit was significantly lower in PTR and it was due to higher production cost involvement. DSR has the potentiality of similar yield to PTR and reduces production cost which increases the net profit of rice production.